2012
DOI: 10.1186/1471-2474-13-111
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation and validation of the Norwegian pain catastrophizing scale in patients with low back pain

Abstract: BackgroundPain catastrophizing has been found to be an important predictor of disability and days lost from work in patients with low back pain. The most commonly used outcome measure to identify pain catastrophizing is the Pain Catastrophizing Scale (PCS). To enable the use of the PCS in clinical settings and research in Norwegian speaking patients, the PCS had to be translated. The purpose of this study was therefore to translate and cross-culturally adapt the PCS into Norwegian and to test internal consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
92
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(119 citation statements)
references
References 34 publications
22
92
4
1
Order By: Relevance
“…The average level of pain catastrophizing was 29.2 (± 13.1) points, corroborating the results of other versions 26,29 and going against those of Fernandes et al 25 . In this study, the average level was 14 points, but the population was of young adults with subacute lower back pain, which may have led to different results.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The average level of pain catastrophizing was 29.2 (± 13.1) points, corroborating the results of other versions 26,29 and going against those of Fernandes et al 25 . In this study, the average level was 14 points, but the population was of young adults with subacute lower back pain, which may have led to different results.…”
Section: Discussionsupporting
confidence: 79%
“…The indexes of separation of items and of individuals showed that the scale is able to divide the people into approximately three levels of catastrophizing (low, medium and high), as described by Fernandes et al 25 and five levels of expression of catastrophizing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature contends that patients who tend to catastrophize perceive pain as stronger than it actually is (1,2). Patients who catastrophize exaggerate pain, ruminate about painful sensations, and show an inability to control pain.…”
Section: Introductionmentioning
confidence: 99%
“…44 The Pain Catastrophizing Scale (PCS) was originally developed in English to assess pain catastrophizing in adults. 35 It has been validated in several languages 12,14,23,25,26,47 and adapted for use in several age groups, 9,38 by adults to assess catastrophizing about their significant other's pain, 4 and by parents to assess catastrophizing about their child's pain. 15 The PCS was adapted for use with Flemish-speaking children aged 9 to 16 years (Pain Catastrophizing Scale-Child [PCS-C] 9 ).…”
mentioning
confidence: 99%